2014
DOI: 10.1155/2014/589586
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Pod Yield and Related Traits of Groundnut (Arachis hypogaeaL.) under Salinity Stress

Abstract: A study was performed using 6 × 6 F1 diallel population without reciprocals to assess the mode of inheritance of pod yield and related traits in groundnut with imposed salinity stress. Heterosis was found for pod number and yield. Data on general and specific combining ability (gca and sca) indicated additive and nonadditive gene actions. The gca: sca ratios were much less than unity suggesting predominant role of nonadditive gene effects. Cultivars “Binachinabadam-2” and “Dacca-1” and mutant M6/25/64-82 had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…This might be due to the additive effects of the genes from the two parents of the respective crosses controlling pod formation and maturity [29]. Kernel yield of the F1s, like the parents, did not show any significant difference at 10 dS/m salinity stress.…”
Section: Discussionmentioning
confidence: 86%
“…This might be due to the additive effects of the genes from the two parents of the respective crosses controlling pod formation and maturity [29]. Kernel yield of the F1s, like the parents, did not show any significant difference at 10 dS/m salinity stress.…”
Section: Discussionmentioning
confidence: 86%
“…This result of relative performance agrees with Haque (2006). Plant height number of leaves and pod yield were gradually decreased in groundnut with increasing salinity dose (Singh et al, 2010;Azad et al, 2014.). Table 2 showed that the relative plant height at growth stages is the highest (97.41%) at pod filling stage and the lowest at vegetative (64.50%) stage which followed by flowering (68.43%) and pre-sowing stage (74.25%), respectively.The interaction effects of variety × salinity dose x growth stage on plant height also presented in Table 2, Dacea-1 and Zhingabadam showed rapid decrease with the increase in salinity than Binachinabadam-3.…”
Section: Results and Discussion Days To Germinationmentioning
confidence: 98%
“…Hence the influence of varying salinity level on maize production needs further intensive studies to correlate the role of tolerant maize varieties on higher yield potential. A comprehensive genetic study is a prerequisite to determine the nature of inheritance of a trait that will lead to choose the right breeding improvement strategy for the crop (Azad et al, 2014). As Table 9.…”
Section: Yieldmentioning
confidence: 99%